PENGARUH PENGALAMAN AUDIT, SKEPTISME PROFESIONAL, DAN PENGETAHUAN AUDIT PADA INDIKASI TEMUAN KERUGIAN DAERAH - Trisna, I Gusti Ayu Agung Manik; Aryanto, Dodik (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
To be able to indicate the findings of a loss of area, an auditor must have extensive experience in conducting audits. The fact auditor experienced in performing the audit process more expert in indicate the existence of fraud and error. So that in conducting the audit process needs to be in the back by an attitude of professional skepticism and a broad knowledge of audit. The study was conducted at the office of the Inspectorate of Klungkung and Karangasem. The sample was selected using a non-probability sampling techniques. Data obtained through the deployment kueisoner to the auditor and analysis techniques used are multiple regression. The results showed testing instruments and classical assumptions are met. Based on the analysis, it is known audit experience, professional skepticism and knowledge audit findings indicated a positive effect on regional losses. These three variables are able to explain the effect of the findings indicated a loss of area equal to 76.9%, while the remaining 23.1% is explained by other variables not included in the research model.
Keywords: Audit Experience, Professional Skepticism, Knowledge Audit, The Findings of Regional Losses